2008
DOI: 10.1007/s12325-008-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress parameters in patients with slow coronary flow

Abstract: Our data showed that in patients with SCF, serum MDA and erythrocyte SOD levels were increased while erythrocyte GSH levels were decreased significantly, compared with NCF patients. These results indicate that free-radical damage may play a role in the pathogenesis of SCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…2 The exact etiopathogenesis of SCF is unclear, but several mechanisms have been proposed including enhanced oxidative stress and inflammation, microvascular dysfunction, small vessel disease, impaired endothelial functions, and diffuse atherosclerosis. [3][4][5][6][7] However, the role of inflammation, oxidative stress, and endothelial dysfunction in the pathogenesis of SCF is well established. 5,8,9 Macrophages and monocytes are the most important cell types for secretion of proinflammatory and prooxidant cytokines at the site of inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The exact etiopathogenesis of SCF is unclear, but several mechanisms have been proposed including enhanced oxidative stress and inflammation, microvascular dysfunction, small vessel disease, impaired endothelial functions, and diffuse atherosclerosis. [3][4][5][6][7] However, the role of inflammation, oxidative stress, and endothelial dysfunction in the pathogenesis of SCF is well established. 5,8,9 Macrophages and monocytes are the most important cell types for secretion of proinflammatory and prooxidant cytokines at the site of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] However, the role of inflammation, oxidative stress, and endothelial dysfunction in the pathogenesis of SCF is well established. 5,8,9 Macrophages and monocytes are the most important cell types for secretion of proinflammatory and prooxidant cytokines at the site of inflammation. 10 In addition, high-density lipoprotein cholesterol (HDL-C) has been shown to defend endothelial cells against the unfavorable effects of low-density lipoprotein (LDL) 11,12 and to prohibit oxidation of LDL molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the histopathological characteristics are similar to coronary atherosclerosis and microvascular dysfunction and free radical damage may be responsible for the pathology (1,7,23). Previous studies reported significantly increased intima-media thickness (IMT) of the carotid artery which is known as a marker of subclinical atherosclerosis in patients with SCF (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, human (31) and animal (32) studies have shown decreased levels of TAS in cases with acute myocardial infarction. Enli et al (23) reported elevated parameters of oxidative stress in patients with SCF compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to OSA, endothelial dysfunction, [20][21][22] oxidative stress, insulin resistance and microvascular dysfunction have been suggested as underlying mechanisms. [23][24][25][26][27][28][29][30][31][32][33][34][35] In addition to these similarities, obesity with or without insulin resistance and lower concentrations of adiponectin and leptin, a hormone involved in the control of body weight and sympathetic nerve activity, have also been found more frequently in both CSFP and OSA. 36 Relationship between the severity of apnea-hypopnea index (AHI) and mean TIMI frame count (TFC).…”
Section: Discussionmentioning
confidence: 99%